A few selected contributions to electron and photon collisions with H2 and H2+. (23rd October 2017) - Schneider, Barry I; Collins, Lee A; Bartschat, Klaus; Guan, Xiaoxu; Hu, S X
Abstract: We discuss a number of aspects regarding the physics of H 2 + and H2 . This includes low-energy electron scattering processes and the interaction of both weak (perturbative) and strong (ultrafast/intense) electromagnetic radiation with those systems.